Competitive adrenal tumors - V O Bondarenko; O E Lutsevich; E V Bondarenko; G A Polyakova (Эндокринная хирургия, 2012)
Contemporary development of two hormonal active tumors in different layers of one adrenal gland is occurring extremely rarely in clinical practice. Authors adduce their own clinical cases of competitive adrenal tumors.